The Impact of Good Corporate Governance on the Financial Performance of Companies Listed on the Indonesia Stock Exchange - Purnamasari; Kharisma (Economy, Business, Finance, Accounting & Management Journal, 2026)
Good Corporate Governance (GCG) is one of the key factors that can enhance the effectiveness of corporate management and drive optimal financial performance. The implementation of good corporate governance is becoming increasingly important for companies listed on the Indonesia Stock Exchange (IDX) as it can improve transparency, accountability, and investor confidence. However, previous research findings on the impact of GCG on financial performance remain inconsistent. Therefore, this study aims to analyze and test the impact of Good Corporate Governance on the financial performance of companies listed on the Indonesia Stock Exchange. This study employs a quantitative approach using secondary data obtained from companies’ annual reports and financial statements for the 2020–2023 period. The research sample was determined using *purposive sampling*. The Good Corporate Governance variable is proxied through independent commissioners, the board of commissioners, institutional ownership, and the audit committee, while financial performance is measured using *Return on Assets* (ROA). Data analysis was conducted using multiple linear regression. The results indicate that Good Corporate Governance has a positive and significant impact on a company’s financial performance. These findings indicate that the implementation of good corporate governance can enhance the effectiveness of oversight, reduce agency conflicts, and support improvements in corporate profitability. Thus, Good Corporate Governance is a critical factor in driving sustainable improvements in corporate financial performance